Factors Related To Self-care Behaviors Among The Elderly groups of Sra Takhe Sub-District Health Promotion Hospital, Banlang Sub-District,Non Thai District, Nakhonratchasima Province - sudarat (Primary Health Care Journal (Northeastern Edition), 2021)
This research is a descriptive research and aimed to study the factors related to self-care behaviors among social bound in Sra Takhe sub-district health promotion hospital, Banlang sub-district, Non Thai district, Nakhon Ratchasima province. The samples is social bound (ADL 12–20 points) were 180 people. Data were collected by interview. Descriptive data were analyzed by descriptive statistics such as frequency percentage and standard deviation, and Pearson’s product-moment correlation coefficient. The results showed that most of the social bound had knowledge about self-care at a high level, 94.4%, attitudes about self-care at a good level, 78.8% and had behaviors to take care of their own health at a good level of 87.2%. The factors related to self-care behaviors among social bound of found Individual factors include age and education level had the related to the self-care behaviors of the social bond with statistical significance at (P-value >0.05). The Knowledge of self-health care and attitudes about self-care had related to the self-care behaviors of the social bond with statistical significance at (r=0.356, 0.275 and P-value <0.01).